Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/jof8020117
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Antiaflatoxinogenic Effects of Cymbopogon citratus, Cymbopogon nardus, and Cymbopogon schoenanthus Essential Oils Alone and in Combination

Abstract: The antifungal and antiaflatoxinogenic activities of the essential oils (EOs) from the leaves of Cymbopogon schoenanthus, Cymbopogon citratus, Cymbopogon nardus, and their pair combinations were investigated. Antifungal susceptibility and the efficacy of paired combinations of EOs were assessed using agar microdilution and checkerboard methods, respectively. Identification and quantification of chemical components of the EOs were carried out by gas chromatography-mass spectrometry and gas chromatography-flame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…niger on plum fruit. Sawadogo et al [ 36 ] reported that Cymbopogon nardus (L.) EO exhibited high antifungal activity against A . flavus and A .…”
Section: Discussionmentioning
confidence: 99%
“…niger on plum fruit. Sawadogo et al [ 36 ] reported that Cymbopogon nardus (L.) EO exhibited high antifungal activity against A . flavus and A .…”
Section: Discussionmentioning
confidence: 99%
“…C. citratus , or lemongrass, exhibits a wide range of biologic activities due to its diverse bioactive compounds. The plant’s antimicrobial properties encompass both antibacterial and antifungal actions, with efficacy against Gram-negative and Gram-positive bacterial strains [ 4 ] and fungi such as Aspergillus spp., Mucor indicus [ 5 ], Botrytis cinerea [ 6 ], and Aspergillus flavus and Aspergillus parasiticus [ 7 ]. Lemongrass demonstrates anti-aspergillosis potential by inhibiting enzymes essential for fungal cell wall synthesis [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plant’s antimicrobial properties encompass both antibacterial and antifungal actions, with efficacy against Gram-negative and Gram-positive bacterial strains [ 4 ] and fungi such as Aspergillus spp., Mucor indicus [ 5 ], Botrytis cinerea [ 6 ], and Aspergillus flavus and Aspergillus parasiticus [ 7 ]. Lemongrass demonstrates anti-aspergillosis potential by inhibiting enzymes essential for fungal cell wall synthesis [ 4 , 5 , 6 , 7 , 8 ]. Lemongrass also shows promise in the realm of human health, with hepatoprotective effects against hepatocellular injury in diabetic rats [ 9 ], cholesterol-lowering potential by preventing gut absorption [ 10 ], and the ability to overcome doxorubicin resistance in cancer cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…16,17,18 In vivo studies have shown antimalarial activity of Cymbopogon citratus in mice. 16,19 Also, Gas chromatography-mass spectrometry (GC-MS) analysis has revealed the presence of cymbopogonol in lemongrass. 20 In this study, the activity of the phytochemicals present in lemongrass was explored against FP2, and cymbopogonol was found to have the best inhibitory potential towards the target.…”
Section: Introductionmentioning
confidence: 99%